Reproduction of the bleak, Alburnus mossulensis in the southern reaches of Euphrates River, Iraq - Aufi, Layla A.; Mohammed, Abdul-Razak M. M.; Jasim, Basim M. (Iraqi Journal of Aquaculture, 2023)
Samples of Alburnus mossulensis were collected from the south part of Euphrates River, Chybaish, Iraq from November 2013 to October 2014 using electro fishing. The spawning period started in February according to GSI values and histological examination for gonads during spawning season. The results of histological examinations revealed that this species has a short spawning season and female ovaries contained different maturing stages of ova, and the maturation started from the post part of gonads according to the space noticed at the middle part of the ovary. Histological examination proved that testes also contain different maturation stages. Blood vessel penetrate lobules with few spermatocytes at the posterior part of the testes whereas the anterior part less mature with disappearing of spermatocytes.